Controlling silver morphology on a cramped optical fiber facet via a PVP-assisted silver mirror reaction for SERS fiber probe fabrication. (15th February 2021) - Long, Yuting; Li, Hong; Yang, Xinxin; Yuan, Yufei; Zheng, Mengjie
Abstract : Controlling the morphology of silver nanoparticles on a cramped and curved optical fiber facet is urgently needed to obtain SERS optical fiber probes with high performance. Abstract : Controlling the morphology of silver nanoparticles on a cramped and curved optical fiber facet is urgently needed to obtain SERS optical fiber probes with high performance. In this work, a fast and simple method, PVP-assisted silver mirror reaction, is employed to synthesize SERS fiber probes. The morphology of silver on a cramped optical fiber facet can be controlled by optimizing the reaction conditions. The influences of reaction conditions, including the PVP/AgNO3 molar ratio, ammonium hydroxide concentration, silver nitrate concentration, type of the reducing saccharide and the pH value of Tollens' solution, on the morphology and SERS performance of the fiber probes were investigated. The results show that silver nanoparticles can be densely distributed on the optical fiber facet with narrow interparticle gaps by varying these reaction parameters. The resultant SERS fiber probe shows high sensitivity and good reproducibility by using 4-aminothiophenol (4-ATP) as the probing molecule. Furthermore, the localized electromagnetic field of silver nanoparticles giving rise to enormous SERS signal amplification was simulated to clarify the SERS performance of the fiber probe. To the best of our knowledge, in situ detection of the analyte in a confined area and a curved channel using the SERS fiber probe is verified for the first time. The obtained SERS fiber probe shows promising applications in flexible detection for early diagnosis of major diseases and critical conditions including confined, remote and hazardous environments.